Pemberdayaan Masyarakat Berbasis Masjid melalui Program Pembuatan Lilin Aromaterapi dari Limbah Minyak Jelantah di Kampung Kiara, Kota Serang-Banten - Sumintak Sumadi; Bendi Setia Budi; Hamzah; Aulia Azfa Jannah; Arif Fortilo; Nikum Sayidah; Amirudin; Sentia Adelia; Salwa Rizkia Fasha; Siti Maesaroh (PADMA, 2025)
Management of used cooking oil waste is one of the environmental issues faced by the people of Kampung Kiara, Serang-Banten City. The lack of knowledge and skills of residents in managing this waste often causes environmental pollution. This community service activity aims to empower kosidahan mothers through a mosque-based program using used cooking oil as raw material for making aromatherapy candles. The method used is Participatory Learning and Action (PLA), which involves the community from the problem identification stage, training, to joint evaluation. The results of the activity show an increase in public knowledge about the dangers of used cooking oil as well as skills in processing it into valuable products. The aromatherapy candles produced are not only environmentally friendly, but also have economic potential as creative household products. This program proves that mosques can function as centers for socio-economic empowerment of the community, as well as encouraging awareness of sustainable waste management.